Penyuluhan refreshment pelaksanaan lesson study dalam meningkatkan kompetensi pedagogik SLB-C se-Kota Makassar - Djoni Rosyidi; Mufa’adi Mufa’adi; Dwiyatmi Sulasminah (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Various pedagogical quality improvement activities by schools, according to the opinion of Servers as facilitators ofLesson Study (LS) Activities in the Province of South Sulawesi, especially in the Madras Makasssar City, which were first heldwere not optimal as expected. Due to the lack of understanding of LS by school leaders and staff, so the implementation is moreor less serious. The success of LS is said to be successful if the school in this case the school leader or his representative (deputyheadmaster in the field of education) the principal / deputy is ready and committed to carry out all activities and rules, if not thenfailure is obtained. It also needs to be understood, that LS is a model of fostering the profession of educators throughcollaborative and continuous assessment of learning based on the principles of collegiality and mutual learning to build learningcommunities. LS is not a learning method or learning strategy, but LS activities can choose and apply various learning methodsthat are appropriate to the situation, conditions, and problems faced by educators. It can also be said as an instrument that is usedto the fullest ability by teachers to improve the quality of teaching. As a result of the implementation of LS teachers began toappear and remember the core of the material to be presented because previously teachers had participated in several LSseminars, the Principal's commitment was very supportive in realizing LS in their schools which had not been carried outperiodically, "Model" teachers formed a formulation team consisting of five members in developing the preparation of theHOTS-based RPP. The drafting team has produced the HOTS RPP which subsequently discussed it back to the teachers andSupervisors (Dedicated) to optimize the RPP as a result of their work along with their evaluation tools. Other teachers asobservers have also made many contributions in the form of contributing constructive suggestions to the model teacher, and themodel teacher receives suggestions for improvement by later in the day. This activity is also to carry out the stages in the "DO"and "SEE" phases. The Development Team (Plan phase), other teachers (observers) and the Principal along with his staff feelrelieved and satisfied that the effort to improve learning through LS activities is really very supportive in improving the quality ofteachers.